Characterization and Genetic Analysis of Mutant Strains of Escherichia coli K-12 Accumulating the Ubiquinone Precursors 2-Octaprenyl-6-Methoxy-1,4-Benzoquinone and 2-Octaprenyl-3-Methyl-6-Methoxy-1,4-Benzoquinone - Young, I. G. (1971)
The ubiquinone precursors, 2-octaprenyl-6-methoxy-1,4-benzoquinone and 2-octaprenyl-3-methyl-6-methoxy-1,4-benzoquinone, were isolated from ubiquinone-deficient mutants of Escherichia coli and identified by nuclear magnetic resonance and mass spectrometry. Mutants accumulating 2-octaprenyl-6-methoxy-1,4-benzoquinone and 2-octaprenyl-3-methyl-6-methoxy-1,4-benzoquinone were shown to carry mutations in genes designated ubiE and ubiF, respectively. The ubiE gene was shown to be cotransducible with metE (minute 75) and close to two other genes concerned with ubiquinone biosynthesis. The ubiF gene was located close to minute 16 by cotransduction with the lip, gltA, and entA genes.